Regularity of Inhomogeneous Quasi-Linear Equations on the Heisenberg Group (Analysis in Theory and Applications, 2021)
We establish Hölder continuity of the horizontal gradient of weak solutions to quasi-linear $p$-Laplacian type non-homogeneous equations in the Heisenberg Group.
Keywords: Non-homogeneous.